Evaluating User Experience E-Commerce Platform Using Hassenzahl Framework - Kikitamara, Sesaria; Wijaya, Stevanus Wisnu (Universitas Sanata Dharma, 2025)
The Hassenzahl framework of UX provides an approach in measuring user experience of a product which covers such the following aspects : be goals, do goals, and motor goals. Yet the further approach for practical implementation in digital product like e-commerce platform is still insufficient. Another approach, the scenario model provides a journey mapping viewing from the user perspective. Thus, generally this method was used to portray the interaction process between user and product. Furthermore, the term of user journey is also commonly used by the UX designer in order to understand what actually the user needs, not just the user want. The solution offered to discuss within this paper is integrating three key elements of Hassenzahl method for every scenario in the e-commerce process. Hopefully the solution as presented on this paper will generate more credible properties and decent tools for developing an efficient, user friendly, and engaging e-commerce application.